Critical Pedagogy Principles in Teaching EFL Reading - Slamet Wahyudi Yulianto (English Review: Journal of English Education, 2015)
This study attempts to reveal how the use of critical pedagogy principles in teaching English as a Foreign Language (EFL) reading facilitates students to think critically. Additionally, it investigates and elaborates the benefits and challenges of using critical pedagogy principles in teaching EFL reading. The three critical pedagogy principles used in this study were dialogic education, democratic classroom, and reading the world and the word. Critical thinking skills and dispositions expected to be performed by the participants were analysis and evaluation skills, open-mindedness, and making reasoned decision. This is a case study design which was conducted in the form of teaching program. The teaching program which consisted of eight meetings was given to 59 EFL sophomores in the Reading in Professional Context class at a private teacher education in Bandung. Data in the form of classroom talks and activities and students‟ responses as well as their critical thinking skills self-assessment were collected by using video recordings, observation notes, interview guideline, students‟ learning journals, and questionnaires. It is revealed that the teaching program has facilitated students to think critically by providing four categories of activity. They are (1) offering problematic topics and reading materials that are linked to the students‟ lives, (2) encouraging students to read between the lines, (3) distributing classroom power, and (4) creating space for students‟ voices to be heard. Meanwhile, there are two benefits of the teaching program, namely (1) language development and (2) new knowledge as well as experience acquisition. However, there are three major challenges in conducting the teaching program that are (1) the lack of classroom-friendly authentic controversial reading materials, (2) the passive culture, and (3) the unpredictable classroom.Keywords: critical pedagogy principles, critical thinking skills, EFL reading class